Position of operant cost affects blue foxes' time budget between sand floor and mesh floor - Koistinen, Tarja; Orjala, Hanna; Mononen, Jaakko; Korhonen, Hannu T. (Applied Animal Behaviour Science, 2009)
v 2009 ok